2013
DOI: 10.1021/ie402724q
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Adsorptive Desulfurization of Light-Irradiated Diesel Fuel over Supported TiO2–CeO2 Adsorbents

Abstract: This study investigates ultra-deep adsorptive desulfurization (ADS) from light-irradiated diesel fuel over supported TiO2–CeO2 adsorbents. A 30-fold higher desulfurization capacity of 95 mL of fuel per gram of adsorbent (mL-F/g-sorb) or 1.143 mg of sulfur per gram of adsorbent (mg-S/g-sorb) was achieved from light-irradiated fuel over the original low-sulfur fuel containing about 15 ppm by weight (ppmw) of sulfur. The sulfur species on spent TiO2–CeO2/MCM-48 adsorbent was identified by sulfur K-edge XANES as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…At the C e of 15 ppmw-S, the q e were 5.15, 2.45 and 0.31 mg/g for 0.3TiO 2 /0.7SiO 2 -UV, Cu-BTC and MIL-100(Fe), respectively. The greatest q e at low C e (0-50 ppmw-S) on 0.3TiO 2 /0.7SiO 2 -UV suggested that the 0.3TiO 2 /0.7SiO 2 adsorbent under UV-irradiation can be a promising approach for the effective deep desulfurization of fuel for ultra-clean fuel production, i.e., <15 ppmw-S (U.S. EPA regulation [2a]), or <1 ppmw-S (on-board fuel cell applications [15]). …”
Section: Adsorption Isotherms Of Dbtmentioning
confidence: 99%
See 2 more Smart Citations
“…At the C e of 15 ppmw-S, the q e were 5.15, 2.45 and 0.31 mg/g for 0.3TiO 2 /0.7SiO 2 -UV, Cu-BTC and MIL-100(Fe), respectively. The greatest q e at low C e (0-50 ppmw-S) on 0.3TiO 2 /0.7SiO 2 -UV suggested that the 0.3TiO 2 /0.7SiO 2 adsorbent under UV-irradiation can be a promising approach for the effective deep desulfurization of fuel for ultra-clean fuel production, i.e., <15 ppmw-S (U.S. EPA regulation [2a]), or <1 ppmw-S (on-board fuel cell applications [15]). …”
Section: Adsorption Isotherms Of Dbtmentioning
confidence: 99%
“…Metal oxide-based adsorbents have caught attentions with plausible regenerability by air oxidation treatment [15]. Watanabe et al [16] developed regenerable mixed TiO 2 -CeO 2 adsorbent that demonstrated high ADS capacity from real fuel, and the adsorption selectivity was enhanced by tuning the Ti/Ce ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods for the treatment of sulphur‐containing fuel, such as hydrodesulphurization (HDS), oxidation, extraction, and adsorption for ultra‐deep desulphurization of fuels. Among the above techniques, adsorptive desulphurization (ADS) is recognized as an emerging alternative technology for ultra‐deep desulphurization due to its simplicity and adaptability to different fuel processors …”
Section: Introductionmentioning
confidence: 99%
“…Among the above techniques, adsorptive desulphurization (ADS) is recognized as an emerging alternative technology for ultra-deep desulphurization due to its simplicity and adaptability to different fuel processors. [7][8][9][10] Amorphous silica from natural resources is widely used as an adsorbent due to its high surface area and high adsorption capacities. [11] The silver supported on TiO 2 -SiO 2 is effective for removing sulphur compounds from diesel fuel.…”
Section: Introductionmentioning
confidence: 99%